Media As Multi Space: Spatial-Based Tourism on Digital Virtual Era - Bramasta Putra Redyantanu (RUAS)
This study aims to map the characteristics and potential uses of digital virtual media as extensions of spatial architecture within the context of tourism. Beyond serving as mere representations, this study argues that digital virtual media function as a transformation of spatial architecture. The concept of multi‑spatiality emphasizes the inseparable relationship between physical and digital architecture. In the context of tourism, architectural objects such as museums are experiential spatial designs that can be further expanded through digital virtual media. This qualitative study uses the Aceh Tsunami Museum as a case study. Through observation, various media‑based modes of representing this architectural object were identified. This study focuses on mapping the characteristics of each media-based spatial model. The findings from this characterization are synthesized into three main concepts: multi-access, multi-user, and multi-time, which together represent an extension of the architectural experience itself. This study positions architecture not only as a physical structure but also as an evolving spatial entity, extending beyond mere duplication to encompass diverse digital and virtual dimensions.